TRANSFORMATION OF APPROACHES TO LABOR RATIONING IN THE OPERATIONAL ACTIVITIES OF ENTERPRISES FROM A MECHANISTIC MODEL TO A HUMANISTIC PARADIGM - KAPINOS, Hennadii; LARIONOVA, Katerina (Herald of Khmelnytskyi National University. Economic sciences, 2025)
This article examines the theoretical and practical aspects of transforming approaches to labor rationing in enterprise operational activities – from a mechanistic model focused on standardization and rigid control to a humanistic paradigm that recognizes the value of human capital and employee autonomy. The historical evolution of labor rationing concepts is analyzed and key factors that led to the transition from viewing workers as elements of production machinery to recognizing them as autonomous professionals are identified. The necessity of changing approaches to rationing in the knowledge economy is substantiated, where intellectual and creative labor predominates, characterized by non-linearity of results, high variability of productivity, and dependence on the psychological state of workers. Contemporary work organization methodologies are systematized, including Agile frameworks, management by objectives, KPI systems, and competency-based approaches. A comprehensive multidimensional model of labor rationing for the knowledge economy is proposed, combining assessment of performance, quality, competencies, innovation, and teamwork. Practical recommendations for the phased implementation of humanistic approaches at Ukrainian enterprises are developed, taking into account cultural and organizational specificities. The main challenges of transformation are identified, including the complexity of measuring creative work quality, risks of manipulating indicators, and the need for cultural changes in organizations. The study demonstrates that the transition to a humanistic paradigm of labor rationing is not an alternative but a necessity for enterprises seeking success in the 21st century economy, particularly in conditions of skilled personnel shortage and competition for talent in the global labor market.